2017
DOI: 10.1523/jneurosci.2968-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Inhibition of Ventral Pallidum Neurons Impairs Context-Driven Salt Seeking

Abstract: . However, it is not known whether the VP is necessary for salt appetite in terms of seeking out salt or consuming salt following sodium depletion. Here, we used a conditioned place-preference procedure to investigate the effects of optogenetically inhibiting the VP on context-driven salt seeking and the consumption of salt following deprivation. Male rats learned to associate one context with sucrose and another context with lessdesirable salt. Following sodium depletion, and in the absence of either sucrose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…Neural manipulations during either the depletion and consumption tests may reveal dissociations between context-driven salt seeking and salt consumption following sodium depletion. One salient example is our prior study (Chang et al , 2017), in which we observed a specific deficit in context-driven salt seeking but not salt consumption following sodium depletion with optogenetic inhibition of the VP.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Neural manipulations during either the depletion and consumption tests may reveal dissociations between context-driven salt seeking and salt consumption following sodium depletion. One salient example is our prior study (Chang et al , 2017), in which we observed a specific deficit in context-driven salt seeking but not salt consumption following sodium depletion with optogenetic inhibition of the VP.…”
Section: Discussionmentioning
confidence: 83%
“…Figure 3 presents what one would expect to observe for a control group of rats in our salt appetite procedure (n = 19 male rats; group means ± SEM; adapted from Chang et al ., 2017). Rats should drink more sucrose than salt over the course of training (Figure 3A).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations